Clinical Events Associated with Acupuncture Intervention for the Treatment of Chronic Inflammation Associated Disorders - Hua Bai; Senlei Xu; Qiulan Wu; Shanshan Xu; Ke Sun; Jiahong Wu; Xuefeng Xia; Yuchen Liu; Hongru Zhang; Shengfeng Lu (Mediators of Inflammation)
Acupuncture is a key component of Chinese medicine. It describes a series of procedures involving the stimulation of skin through penetration of fine, single-use, sterile needles that result in the release of neurotransmitters. Although its use is on the growing trend, considerable controversy surrounds its value as a therapy. Standard randomized controlled trials that adhere to the accepted criteria should be conducted in the future to ensure the effectiveness of acupuncture. This article summarizes the current evidence regarding the use of acupuncture. It includes a description of the history, mode of operation, treatment of a variety of chronic disorders related to inflammation, and future directions for acupuncture use. Published clinical trials support the view that acupuncture is a possible candidate for the treatment of several chronic inflammation-related disorders.